Requirement for chitin biosynthesis in epithelial tube morphogenesis - W. Patrick Devine; Barry Lubarsky; Ken Shaw; Stefan Luschnig; Lisa Messina; Mark A. Krasnow (2005)
Many organs are composed of branched networks of epithelial tubes that transport vital fluids or gases. The proper size and shape of tubes are crucial for their transport function, but the molecular processes that govern tube size and shape are not well understood. Here we show that three genes required for tracheal tube morphogenesis in Drosophila melanogaster encode proteins involved in the synthesis and accumulation of chitin, a polymer of N -acetyl-β- d -glucosamine that serves as a scaffold in the rigid extracellular matrix of insect cuticle. In all three mutants, developing tracheal tubes bud and extend normally, but the epithelial walls of the tubes do not expand uniformly, and the resultant tubes are grossly misshapen, with constricted and distended regions all along their lengths. The genes are expressed in tracheal cells during the expansion process, and chitin accumulates in the lumen of tubes, forming an expanding cylinder that we propose coordinates the behavior of the surrounding tracheal cells and stabilizes the expanding epithelium. These findings show that chitin regulates epithelial tube morphogenesis, in addition to its classical role protecting mature epithelia.